Application of Sustainable Tourism: A Study on the Community of Widosari Yogyakarta Tourism Village - R Kusherdyana; Syaeful Muslim (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The phenomenon of sustainable tourism has become a critical global issue. This research aims to explore the community's level of understanding and implementation of sustainable tourism in Widosari Tourism Village, Yogyakarta. This research uses a qualitative approach. The research subjects in this study were five young people who were actively developing the Widosari Tourism Village in Yogyakarta. The research results show that the Widosari Village community's understanding of the concept of sustainable tourism is quite good. In connection with the implementation of sustainable tourism, the people of Widosari Village have taken several positive actions in managing natural resources, preserving culture, and involving the community in the tourism business. However, challenges remain, especially related to water management, holistic cultural preservation, souvenir sales, and the lack of tourism impact monitoring programs. Joint efforts between stakeholders and village government support are needed to overcome this challenge and ensure sustainable tourism that provides long-term benefits for the people of Widosari Village.